Clinical efficacy of THA with dual mobility cup vs. hemiarthroplasty in elderly patients with femoral neck fracture: a retrospective study - Xiao, Kai; Liu, Songyang; Liang, Boran; Li, Shuming; Liu, Xinyan; Chen, Jing (Frontiers in Surgery, 2025)
ObjectiveTo compare the clinical efficacy of total hip arthroplasty (THA) with or without dual mobility cup (DMC) vs. hemiarthroplasty (HA) in elderly Asian patients with acute femoral neck fracture (FNF).MethodsData of 284 elderly FNF patients treated at our institution from January 2017 to December 2021 were retrospectively collected. Patients were divided into the DMC-THA group (THA with DMC, n = 102), C-THA group (conventional THA without DMC, n = 88), and HA group (n = 94). The study assessed perioperative outcomes, hip functional recovery, treatment satisfaction, long-term prognosis, and quality of life.ResultsThe Harris Hip Scores in the DMC-THA group were significantly higher than those in the C-THA and HA groups at 3 months, 6 months, and 1 year postoperatively (P < 0.05). The satisfaction rate in the DMC-THA group (92.2%) was significantly higher compared to the C-THA (81.8%) and HA groups (80.9%) (P < 0.05). At 1 year post-surgery, the DMC-THA group demonstrated a significantly lower dislocation rate (2.0% vs. 9.1%) and superior mobility compared to the C-THA group (P < 0.05). Additionally, the DMC-THA group exhibited significantly better mobility and reduced pain/discomfort compared to the HA group (P < 0.05).ConclusionTHA with DMC offers superior joint function recovery, a lower dislocation rate, and improved quality of life compared to conventional THA and HA, positioning it as a preferred surgical option for elderly patients with acute FNF.